Design of Science Process Skills Instruments Reaction Rate Material: Rasch Model Approach - Apriyani, Difva; Aini, Faizah Qurrata (Journal of Educational Sciences, 2025)
The assessment process conducted by teachers tends to focus on understanding chemistry rather than the students' science process skills. This is because there are no available assessment instruments to measure students' science process skills, resulting in the chemistry learning outcomes in the independent curriculum not being fully achieved. This research aims to develop an assessment instrument that can measure students' science process skills on the topic of reaction rates. This instrument was developed using ten stages of the Rasch model and consists of 24 multiple-choice questions based on the aspects of science process skills in the independent curriculum. Field test results were analyzed using Ministep software, and it was found that all questions were declared valid because they met the MNSQ, ZSTD, and Pt Mean Corr criteria. The reliability value of 0.84 falls into the good category, and it also has good difficulty and discrimination indices according to the Rasch model. The results of the study indicate that the developed science process skills assessment instrument is suitable for use.